Tingkat Orientasi Olahraga Mahasiswa Menggunakan Sport Education Musim Bola Tangan - Effendy, Fauzan; Ramadhan, Riki; Setiawan, Anang; Oktriani, Seni (YLPK Mahardhika, 2024)
This research aims to determine the level of students sports orientation using Sport Education (SE) on handball season based on the sports orientation subscale within the team roles, and the sports orientation subscale within each team involved. The research method uses a descriptive quantitative approach. The participants involved were 48 students who were taken using a purposive sampling technique from one of the sports study programs in Indramayu. The research instrument used the Sport Orientation Questionnaire (SOQ) for students majoring in sports. Data analysis techniques using descriptive statistics. The results of the study concluded that the level of sports orientation of students using the handball season SE tends to be in the sufficient category and the sports orientation of students using the handball season SE is based on the sports orientation subscale which is also seen from in the team roles and each team involved is more influenced by goal orientation. In order to carry out further research using SE in individual sports where the underlying sports orientation has not yet been revealed.